The effects of gamma irradiation on threshold voltage and channel mobility models of PMOS - Kerdpradist, Amonrat; Titiroongruang, Wisut; Atiwongsangthong, Narin; Muanghlua, Rangson; Ruangphanit, Anucha (My University, 2018)
This paper presents the effects of gamma irradiation on threshold voltage and mobility models of PMOS. The devices with a gate oxide thickness of 15 nm fabricated in an 0.8-micron CMOS technology were measured and tested. The electrical properties were collected pre-irradiation and after the exposure by a60Co gamma-ray source in the dose range of 1 to 10 kGy, transient dose = 290.68 Gy/hr. The results show that the threshold voltage of big MOS at zero substrate bias (VT0) increased approximately 28%, but the low field surface mobility (UO) and the maximum transconductance parameter (K0) decreased in the same value by 7.5% and the THETA (? ) parameter decreased by 28%. All parameters caused the saturation drain current of big MOS to decrease 16%. For short channel effects, the saturation drain current decreased more. Finally, the short channel model parameter should be investigated and discussed in future.
Keywords: Gamma Irradiated; P-Channel MOSFET; Surface Mobility; Threshold Voltage